(untitled) (Fiep Bulletin - online, 2014)
The main objective of this study is to make a comparison between the sports legislation, applied to young practitioners, of the Brazil and France. Through preliminary observational research, it became possible to expose the confrontation of the two social realities presented. We shall demonstrate, through the exposure of the education code and the sports code, the strong incentive of france to build a successful career, focused in both the performance and the development of the ethical principles of society, and also paying attention to important health matters. In contrast, although the Brazilian legislator preaches the full distinction between high performance sport and educational sport, which aims for the integral development of the individual and the formation of their citizenship, it’s possible to see that our actual reality is very different from what is idealized in the Article 217 of the Federal Constitution of the Federal Republic of Brazil. Finally, taking into account the treatment provided by the French government to the promotion of school sports and caution used for the treatment of young people, we were able to establish our interventional proposal for the cases of physical and symbolic violence within the context of this sport.